Age Limit for the Managing Director : Proposed Amendment of Section 14(c) of the By-Laws. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
At the request of Executive Directors, and in light of the publicly announced nomination of a candidate who is over the age of sixty-five for the post of Managing Director, I am circulating the attached draft Report of the Executive Board to the Board of Governors. The draft report proposes an amendment of Section 14(c) of the By-Laws regarding the age limit for the Managing Director.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet